2016
DOI: 10.1002/jgm.2925
|View full text |Cite
|
Sign up to set email alerts
|

A kidney injury molecule‐1 (Kim‐1) gene reporter in a mouse artificial chromosome: the responsiveness to cisplatin toxicity in immortalized mouse kidney S3 cells

Abstract: BackgroundKidney injury molecule‐1 (Kim‐1) has been validated as a urinary biomarker for acute and chronic renal damage. The expression of Kim‐1 mRNA is also activated by acute kidney injury induced by cisplatin in rodents and humans. To date, the measurement of Kim‐1 expression has not fully allowed the detection of in vitro cisplatin nephrotoxicity in immortalized culture cells, such as human kidney‐2 cells and immortalized proximal tubular epithelial cells.MethodsWe measured the augmentation of Kim‐1 mRNA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 52 publications
0
16
0
1
Order By: Relevance
“…Two of the most promising biomarkers of AKI are KIM-1 [19] and NGAL [20]. We found that pretreatment with FF inhibited the overexpression of KIM-1 and NGAL in renal tissue of LPS-induced AKI mice.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Two of the most promising biomarkers of AKI are KIM-1 [19] and NGAL [20]. We found that pretreatment with FF inhibited the overexpression of KIM-1 and NGAL in renal tissue of LPS-induced AKI mice.…”
Section: Discussionmentioning
confidence: 76%
“…We found that pretreatment with FF inhibited the overexpression of KIM-1 and NGAL in renal tissue of LPS-induced AKI mice. The release of KIM-1 and NGAL from damaged renal tissue also leads to the downstream activation of transcription factors that regulate the expression of inflammatory cytokines and chemokines [19,21].…”
Section: Discussionmentioning
confidence: 99%
“…The MI-MAC has also been transferred into HepG2 cells to verify cytotoxicity levels via luciferase reporter assay [69]. The MI-HAC/MAC system can be used in various cell types and has successfully achieved the insertion of large GLVs such as PACs and BACs and multiple genes into the MI-HAC/ MAC [70][71][72]. Although limitations exist regarding the available drug-resistant genes for five GLVs loading onto the MI-HAC/MAC vector, this was solved by reusing the same drug-resistant genes by disrupting them with genome editing technology (Honma et al, 2017, unpublished data).…”
Section: Gene-loading Techniques For Hacs/macsmentioning
confidence: 99%
“…KIM-1 has been found to be a useful biomarker for kidney injury [ 3 , 4 ]. In vivo , KIM-1 can be upregulated in proximal tubular cells in response to a variety of injuries [ 5 , 6 ]. A greater understanding of what regulates the KIM-1 locus could lead to more insight into kidney injury.…”
Section: Introductionmentioning
confidence: 99%